2019
DOI: 10.3389/fonc.2019.01218
|View full text |Cite
|
Sign up to set email alerts
|

An Externally Validated Nomogram for Predicting Lymph Node Metastasis of Presumed Stage I and II Endometrial Cancer

Abstract: Background: Optimal management for endometrial cancer in patients with clinically negative lymph nodes is still under debate. Several prediction models for lymphatic dissemination of early-stage endometrial cancer have been developed. However, external validation is rare, and decision curve analysis has hardly been applied for these models.Objective: To develop and validate a nomogram to predict lymph node metastasis of presumed stage I and II endometrial cancer.Study Design: The prediction nomogram was develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…One recent study constructed a nomogram for predicting the overall survival and found the nomogram was more accurate than the Mayo criteria. 14 Other studies focused on a risk matrix model to identify high-risk parameters necessitating lymphadenectomy and to decide the risks and benefits of lymphadenectomy. 15 A long-term argument against routine lymph node dissection was that the procedure could cause several complications such as bowel obstruction, deep venous thrombus and chronic lymphedema.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study constructed a nomogram for predicting the overall survival and found the nomogram was more accurate than the Mayo criteria. 14 Other studies focused on a risk matrix model to identify high-risk parameters necessitating lymphadenectomy and to decide the risks and benefits of lymphadenectomy. 15 A long-term argument against routine lymph node dissection was that the procedure could cause several complications such as bowel obstruction, deep venous thrombus and chronic lymphedema.…”
Section: Discussionmentioning
confidence: 99%
“…Individualized mathematical nomograms have been widely adopted as auxiliary tools to guide clinical decision making in medical fields [11][12][13][14]. In 2014, AlHilli et al developed nomograms stratified histologically to predict the overall survival of EC patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study from our institute also revealed that cervical stromal invasion is an independent risk factor for LNM (in addition to LVSI, tumor grade, and myometrial invasion) in EC patients and may have an important role in predicting LNM. [28] . Another study also suggested that cervical stromal invasion was useful in estimating LNM risk for EC patients and directing therapeutic strategies [29] .…”
Section: Discussionmentioning
confidence: 99%